Distortions of Body Perception during Immersion in Computer Virtual Reality Using Full-Body Tracking - Andrey V. Varlamov; Natalya V. Yakovleva (Peoples' Friendship University of Russia (RUDN University), 2022)
Person's immersion in computer virtual reality (VR) is accompanied by numerous distortions in his/her perception due to the replacement of sensory stimuli coming through visual, auditory and partially proprioceptive channels. In this case, the person's own body becomes an immersion tool, since its movements indirectly affect the movement of the avatar in VR. Performing actions in VR on behalf of the avatar contributes to the appearance of distortions in the perception of one's own body due to the diffuse effect of actualizing the operational image at the moment of purposeful activity (the subjective body image is modified in accordance with the need to adapt to VR conditions). There are various ways of immersing in VR, taking into account the different degree of involvement of individual parts of the recipient's real body in controlling a digital character. Thus, the full-body tracking (FBT) technology is becoming widespread, allowing the use of almost all human gross motor skills for projection onto the movements of the avatar. The purpose of the study was to establish the specific features of the distortion of a person's perception of the size of his/her own body, after its being immersed in computer virtual reality, and the control over the avatar using the FBT technology. The study was conducted in two stages (in 2020 and 2021) in order to compare the intensity and direction of body image distortions of the subjects when they were immersed with and without the FBT technology. The OhShape VR app for mobile immersion without FBT and a modification of the VR Chat app for mobile immersion with FBT were used as experimental exposures. Psychometric data on the subjects' perception of their own bodies were obtained using the psychometric data on the subjects' perception of their own bodies were obtained using Moshe Feldenkrais' methods for physical measurements. According to the results of the study, the use of FBT during immersion in VR leads to distortions in the perception of various body sizes by the subjects, including the trunk and legs, while mobile immersion without the use of FBT only causes distortions in the perception of the dimensions of the upper shoulder girdle. It should be noted that this observation testifies to the connection of distortions with the facts of the involvement of the corresponding parts of the real body of the subjects in the process of controlling the avatar. It is concluded that there are specific distortions in the perception of a person's own body when being immersed in VR using FBT. Finally, an assumption is made about the possible connection of these distortions with the success of performing intra-environment mobile tasks.